2008
DOI: 10.1016/j.ecresq.2008.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive and effortful control and academic self-efficacy beliefs on achievement: A longitudinal study of 1st through 3rd graders

Abstract: The linkages between self-regulatory processes and achievement were examined across three years in 733 children beginning at 1 st grade (M = 6.57 years, SD = .39 at 1 st grade) who were identified as lower achieving in literacy. Accounting for consistencies in measures (from one year prior) and for influences of child's age, gender, IQ, ethnicity and economic adversity on achievement, results indicate that adaptive/effortful control at 1 st grade contributed to both academic self-efficacy beliefs at 2 nd grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
123
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(141 citation statements)
references
References 66 publications
12
123
2
4
Order By: Relevance
“…In the study, there were 733 first grade students examined during three years. According to the result of this study, self-efficacy beliefs were positively correlated with reading and math within and across time (Liew et al, 2008, p.515).…”
Section: Academic Successmentioning
confidence: 95%
“…In the study, there were 733 first grade students examined during three years. According to the result of this study, self-efficacy beliefs were positively correlated with reading and math within and across time (Liew et al, 2008, p.515).…”
Section: Academic Successmentioning
confidence: 95%
“…Theories on achievement motivation and achievement emotions suggest that students' affective and behavioral responses in achievement situations are influenced by their beliefs, expectations, interests, and goals (e.g., Bandura, 1993;Dweck & Leggett, 1988;Pekrun, 2006). Research on the role of temperament in this process has grown in the past decade (e.g., Chang & Burns, 2005;Elliot & Pekrun, 2007;Elliot & Thrash, 2002;Rothbart & Hwang, 2005), but especially among children in the beginning of their school career, the number of studies on the relationship between students' temperament and their achievement-related TEMPERAMENT, AFFECTS, AND BEHAVIORS 7 affects and behaviors is limited (for exceptions, see Chang & Burns, 2005;Harris, Robinson, Chang, & Burns, 2007;Liew et al, 2008).…”
Section: Temperament In the School Contextmentioning
confidence: 99%
“…Temperament has been examined in relation to, for example, students' achievement, student-teacher interactions, problem behavior, and psychosocial functioning at school (e.g., Eisenberg et al, 2009;Nelson, Martin, Hodge, Havill, & Kamphaus, 1999;Valiente, Lemery-Chalfant, & Swanson, 2010;Zhou, Main, & Wang, 2010). For example, studies among kindergartners and elementary school students have found good self-regulation or high effortful control to be positively related to students' self-efficacy (Liew, McTigue, Barrois, & Hughes, 2008), academic competence (Liew et al, 2008;Valiente et al, 2010;Zhou et al, 2010), classroom participation (Valiente, Lemery-Chalfant, Swanson, & Reiser, 2008), school liking (Valiente, Lemery-Chalfant, & Castro, 2007), and work habits (Curby, Rudasill, Edwards, & Pérez-Edgar, 2011). Kindergarten and elementary school students' shyness or behavioral inhibition, TEMPERAMENT, AFFECTS, AND BEHAVIORS 6 on the other hand, has been shown to be negatively related to their academic engagement (Hughes & Coplan, 2010) and achievement (Hughes & Coplan, 2010;Valiente et al, 2010).…”
Section: Temperament In the School Contextmentioning
confidence: 99%
“…Within the temperament tradition, most researchers have used questionnaire data when investigating the link between self-regulation and academic achievement (e.g., Kurdek & Sinclair, 2000;Martin & Holbrook, 1985;Martin, Nagle, & Paget, 1983;Normandeau & Guay, 1998;Schoen & Nagle, 1994;Valiente, Lemery-Chalfant, & Castro, 2007;Valiente, LemeryChalfant, Swanson, & Reiser, 2008;Zhou et al, 2010), although not exclusively (e.g., Liew, Chen, & Hughes, 2010;Liew, McTigue, Barrois, & Hughes, 2008). In addition, these studies did not distinguish between hot and cool forms of self-regulation, as general measures including both aspects were used.…”
Section: Attention Controlmentioning
confidence: 99%